2020
DOI: 10.1084/jem.20200137
|View full text |Cite
|
Sign up to set email alerts
|

PDGFA-associated protein 1 protects mature B lymphocytes from stress-induced cell death and promotes antibody gene diversification

Abstract: The establishment of protective humoral immunity is dependent on the ability of mature B cells to undergo antibody gene diversification while adjusting to the physiological stressors induced by activation with the antigen. Mature B cells diversify their antibody genes by class switch recombination (CSR) and somatic hypermutation (SHM), which are both dependent on efficient induction of activation-induced cytidine deaminase (AID). Here, we identified PDGFA-associated protein 1 (Pdap1) as an essential regulator … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 138 publications
0
5
0
Order By: Relevance
“…CH12 is a well-characterized mouse B cell lymphoma line that recapitulates the molecular mechanism and regulation of CSR ( Nakamura et al, 1996 ). Furthermore, CH12 cells display a stable near-diploid genome that can be easily and efficiently manipulated by somatic gene targeting ( Delgado-Benito et al, 2020 ; Delgado-Benito et al, 2018 ; Sundaravinayagam et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…CH12 is a well-characterized mouse B cell lymphoma line that recapitulates the molecular mechanism and regulation of CSR ( Nakamura et al, 1996 ). Furthermore, CH12 cells display a stable near-diploid genome that can be easily and efficiently manipulated by somatic gene targeting ( Delgado-Benito et al, 2020 ; Delgado-Benito et al, 2018 ; Sundaravinayagam et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, depletion of PDAP1 in B cells also caused a sustained expression of ATF4 and induction of ATF4 stress response transcriptional program, [ 62 ] and our data showed that PDAP1 depletion in basal‐like breast cancer induced ferroptotic cell death and significantly reduced tumor growth in xenograft model (Figure 4 ). Knockdown of PDAP1 in colorectal cancer also inhibited tumor growth in PDX model but had a minor effect, if at all, on apoptosis in cultured cells.…”
Section: Discussionmentioning
confidence: 58%
“…Interestingly, although the PDAP1 mRNA contains a CDS that measures only 546 nucleotides in length, its 3′ UTR is instead much larger (more than 2 kb), pointing toward a highly regulated expression for this protein mediated both by miRNAs as shown in this study and potentially also through extensive cross-regulation with other RBPs, as shown for many other instances of RBP regulation [ 57 ]. In murine B lymphocytes, PDAP1 was shown to protect mature B cells from stress and to favor antibody diversification, although no clear mechanism of action could emerge, most likely due to the high number of genes that were affected both positively and negatively in the absence of PDAP1 [ 60 ]. Such large changes in the transcriptome of cells lacking PDAP1 are likely to be the result of a complex pattern of direct and indirect effects.…”
Section: Discussionmentioning
confidence: 99%